A novel endoloop system for closure of colonic mucosal defects through a single-channel colonoscope - Wang, Jiankun; Zhao, Lili; Wang, Xiang; Liu, Li; Wang, Min; Fan, Zhining (Endoscopy, 2017)
Background and study aims Successful closure of the postoperative mucosal defect is crucial for endoscopic treatment. The purse-string suture strategy via a double-channel endoscope has been recommended as being both safe and feasible for large gastrointestinal mucosal defects. However, for colonic treatment, use of a single-channel colonoscope is more popular because of its longer length and greater flexibility. A novel pre-detached endoloop system was therefore developed for endoscopic purse-string suture closure via a single-channel endoscope. This study evaluated its feasibility and efficacy, especially for right colonic mucosal defects.Patients and methods A total of 18 patients with colonic defects post-endoscopic submucosal dissection (ESD) were treated using the single-channel endoscope method.Results All mucosal defects were successfully closed using the novel closure technique. No severe complications, such as massive intraoperative bleeding, delayed bleeding, peritonitis, or perforation, were recorded. All patients recovered well after ESD and left the hospital within 7 days.Conclusions This novel pre-detached endoloop strategy via a single-channel endoscope was safe and feasible for the closure of colonic mucosal defects using an endoscopic purse-string suture.